De novo hepatocellular carcinoma of liver allograft: A neglected issue. Issue 1 (1st February 2015) - Trevisani, Franco; Garuti, Francesca; Cucchetti, Alessandro; Lenzi, Barbara; Bernardi, Mauro
Highlights De novo hepatocellular carcinoma after liver transplant is a rare event. Recurrence of liver disease in the allograft is a major risk factor for this tumor. This tumor generally occurs after a longer lapse of time than recurrence. Only molecular profiling techniques distinguish recipient origin from donor origin. Prevention relies on the effort to prevent/cure recurrent disease in the allograft.